2015
DOI: 10.2298/apt1546065p
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and sugar profiles of various barley cultivars (Hordeum vulgare)

Abstract: The lipid components and soluble sugars in flour samples of different cultivars of barley (Hordeum vulgare), involving winter malting barley, winter forage barley, spring barley, and hulless barley, were identified). Fatty acids were extracted from flour samples with n-hexane, and derivatized into volatile methyl esters, using TMSH (trimethylsulfonium hydroxide) in methanol. Soluble sugars were extracted from defatted and dried samples of barley flour with 96% ethanol, and further derivatized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The application of hierarchical cluster analysis proved a high degree of correlation similarity among the investigated flour samples of the barley cultivars, according to their FA and soluble sugar content. They concluded that there is a possibility of distinguishing flours made from barley, though not reaching to particular barley varieties, just by the analysis of the contents of FA and soluble sugars (Pastor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The application of hierarchical cluster analysis proved a high degree of correlation similarity among the investigated flour samples of the barley cultivars, according to their FA and soluble sugar content. They concluded that there is a possibility of distinguishing flours made from barley, though not reaching to particular barley varieties, just by the analysis of the contents of FA and soluble sugars (Pastor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%